Current developments in grain science. Review - E. P. Meleshkina; L. V. Vanina; I. S. Vitol (Пищевые системы, 2024)
An analytical review of publications on the most relevant and promising areas in the field of grain science is presented: innovative technologies for processing cereals, legumes and oilseeds, obtaining composite types of flour and cereals with a balanced composition and functional properties; assessment of their technological, biochemical, rheological and organoleptic indicators. The authors examined options for their use in the production of fortified flour and cereal products for both general and special purposes; enzymatic methods for modifying by-products (secondary products) of grain and grain mixtures processing; the use of microbial enzyme preparations with cellulolytic, proteolytic and phytase action as a tool for deep processing of by-products (secondary raw materials) to obtain grain hydrolysates and structurally modified bran — valuable components for increasing the nutritional and biological value of food products and feed, as well as a source of available nitrogen and phosphorus nutrition for yeast in fermentation technologies; development of methods for determining norms and duration of safe storage of grain and grain products — wheat flour and semolina, based on the acid value of fat; assessment of the quality and microbiological safety of grain; development of requirements for the targeted use of bakery, confectionery, pasta, and culinary flour; scientifically based approaches to measures to protect grain reserves from pests. An analysis of publications that reflect the most important and pressing issues in grain science demonstrates the close relationship between fundamental and applied research, which is generally aimed at ensuring food security and maintaining public health.